2004
DOI: 10.1074/jbc.m404937200
|View full text |Cite
|
Sign up to set email alerts
|

Selected Non-steroidal Anti-inflammatory Drugs and Their Derivatives Target γ-Secretase at a Novel Site

Abstract: ␥-Secretase is a multi-component enzyme complex that performs an intramembranous cleavage, releasing amyloid-␤ (A␤) peptides from processing intermediates of the ␤-amyloid precursor protein. Because A␤ peptides are thought to be causative for Alzheimer's disease, inhibiting ␥-secretase represents a potential treatment for this neurodegenerative condition. Whereas inhibitors directed at the active center of ␥-secretase inhibit the cleavage of all its substrates, certain non-steroidal antiinflammatory drugs (NSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
168
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(184 citation statements)
references
References 48 publications
12
168
1
3
Order By: Relevance
“…NSAIDs modulate the cleavage site positions of SPP and ␥-secretase on their substrates without inhibiting enzyme activity, and it therefore seems likely that they affect the active site indirectly, if at all. Consistent with this, it was reported that displacement of [ 3 H]L-685,458 by NSAIDs from ␥-secretase is noncompetitive (18,37). We showed that noncompetitive displacement of [ 3 H]L-685,458 by sulindac sulfide also occurred for SPP (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…NSAIDs modulate the cleavage site positions of SPP and ␥-secretase on their substrates without inhibiting enzyme activity, and it therefore seems likely that they affect the active site indirectly, if at all. Consistent with this, it was reported that displacement of [ 3 H]L-685,458 by NSAIDs from ␥-secretase is noncompetitive (18,37). We showed that noncompetitive displacement of [ 3 H]L-685,458 by sulindac sulfide also occurred for SPP (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…If so, the presence of SPP might account for the incomplete displacement of [ 3 H]L-685,458 observed for selective ␥-secretase inhibitors (18), thus calling into question the conclusion that the catalytic active site and the allosteric binding site are present in a 2:1 molar ratio (18). Furthermore, it seems likely that earlier studies of this radioligand in whole cell extracts may have detected predominantly SPP binding rather than ␥-secretase binding (17,37 From the drug discovery perspective, similar pharmacology between ␥-secretase and SPP suggests the potential for off-target liabilities. Additional studies would be needed to understand to what extent inhibitor binding affects enzyme function in vivo and to determine what consequences, if any, would arise from dosing a nonselective drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFK167 and sulindac sulfide are thought to shift the predominant cleavage site, probably through allosteric effects induced by direct PS binding (38,47,50,51). Several of our observations suggest that the effects of PS1 mutations and the allosteric effects of ␥-secretase inhibitors are likely to be tightly related, and we speculate that these effects might even be mediated by a shared mechanism.…”
Section: Discussionmentioning
confidence: 68%
“…Compounds, like the sterols that naturally intercalate within the lipid bilayer, are known to affect many membrane functions. Recently, many investigators have reported that a class of polycyclic compounds known as nonsteroidal antiinflammatory drugs (NSAIDS) block the production of A␤ peptides in animals models of AD and cultured cells (37)(38)(39). It has been claimed that NSAIDS block A␤ production by affecting the conformation of PS1 (40), but it is also conceivable that NSAIDS might in some way modify interactions between intramembranous peptide segments.…”
Section: Discussionmentioning
confidence: 99%